Recanalization of Chronic Extrahepatic Portal Vein Obstruction in Pediatric Patients Using a Minilaparotomy Approach. Issue 3 (March 2019) - Muratore, Sydne; Flanagan, Siobhan; Hunter, David; Acton, Robert
ABSTRACT: Purpose: Extrahepatic portal vein obstruction (EHPVO) is the most frequent cause of portal hypertension in children. Some patients are not amenable to meso-Rex bypass and alternative surgeries do not restore physiologic flow. We aim to demonstrate the feasibility and safety of minilaparotomy for recanalization of chronic EHPVO. Methods: This 2013–2015 single-center, retrospective review included pediatric patients with chronic EHPVO who underwent minilaparotomy, mesenteric vein access, and attempted recanalization of the occluded portal vein. Outcomes included portal patency, resolution of variceal bleeding, size and number of varices, spleen size, and platelet count. Results: There were 6 EHPVO patients. The median age was 9.9 years and median duration of EHPVO was 7 years (3–16 years). EHPVO etiologies were liver transplantation (50%), idiopathic (33%), and umbilical vein catheterization (17%). Four patients (67%) had successful portal vein recanalization and stenting. At last follow-up [median 3.1 years (2.2–4.3 years)] all successfully recanalized patients had patent portal vein stents and resolution of varices and variceal bleeding. The median reduction in spleen size was 26%, with improvement in platelet counts (50–310/μL). The 2 patients with an idiopathic etiology may have never had a main extrahepatic portal vein based on imaging, and both were unable to be recanalized. Conclusions: Recanalization and stenting of a prolonged occlusion of the portal vein via a minilaparotomy approach is feasible, safe, and may provide an alternative to shunt surgery or endoscopic therapy in selected patients.